Interpretations of Greek mythology - Bremmer, Jan N. (Routledge, 1988)
The innovative work of Walter Burkett and the 'Paris school' of Jean-Pierre Vernant has led to renewed interpretation of the Greek myths. This collections of essays avoids monolithic or exclusively structuralist interpretations. This book should be of interest to teachers and students of Greek drama and mythology.